Are Vitamin Beverages Good for Dental Health? - A-Reum Kang; Su-Hee Park; Jung-Woong Woo; Da-Jung Hong; Kyu-Ri Kim; Chi-Yeong Sung; Ji-Yeon Woo; Ju-Hui Jeong; Eun-Ha Jung (The Korean Society of Dental Hygiene Science, 2020)
Background: Although the consumption of vitamin beverages has increased because of the recent interest in health and beauty, guidelines addressing appropriate consumption habits are lacking. Thus, the aim of this study was to investigate the erosive potential of several vitamin beverages and to propose guidelines for the appropriate intake of these drinks.Methods: Five vitamin beverages were selected after a pre-investigation of the current beverage market. Coca-Cola and mineral water were selected as the control beverages. The pH of the beverages was measured with a calibrated pH meter, and the titratable acidity (TA) was determined by using 1 M sodium hydroxide to reach pH 5.5 (TA5.5) and 7.0 (TA7.0). The screening method suggested by the International Organization for Standardization was used to measure pH variation (𝚫pH) by using an under-saturated hydroxyapatite solution to determine the difference between the initial and final pH of the screening solution. All measurements were performed in triplicate.Results: All vitamin beverages tested in this study exhibited a low pH (2.53∼2.99), similar to Coca-Cola, which is known to be a highly acidic beverage. The highest TA5.5 and TA7.0 values of the vitamin beverages were 7.03 ml and 8.81 ml, respectively. The largest change in pH determined by using the screening solution was found in Bacchus D (𝚫pH 1.44±0.05). The mean 𝚫pH of the vitamin beverages was 1.12±0.29, which was higher than that of Coca-Cola (positive control, 𝚫pH 0.58±0.05).Conclusion: Vitamin beverages exhibited an erosive potential capable of damaging enamel surfaces. Therefore, the frequency of vitamin beverage intake should be limited, and individuals consuming these drinks should try to restore normal oral pH as quickly as possible.